Seminar on fast tracking the planning, design and construction of waste water projects Friday 11th June 1993 at the Institution of Civil Engineers, London. (Thomas Telford, 1993)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present.